A case report on adrenocortical carcinoma - M., Gowri; Girijavallabhan, Nair Prashant; J., Arya (International Surgery Journal, 2021)
Adrenocortical carcinoma is a rare entity and usually diagnosed at later stages which poses a treatment dilemma and usually results in a bad prognosis. It is the second most aggressive endocrine malignancy after anaplastic thyroid carcinoma. Here we report a case in a young male diagnosed incidentally on an ultrasound scan done for abdominal pain. On examination his abdomen was soft with no obvious mass palpable. We are reporting a brief summary of the diagnosis, work up and management of this rare entity in the hope that it may shed some more light on the appropriate management of this elusive condition.